DEVELOPMENT OF COOPERATIVE LEARNING MODELS MORALS BASED IN CURRICULUM 2013 - Neny Suharni Sofyan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study investigates the development of a moral-based cooperative learning model within the implementation of the 2013 Curriculum in elementary schools. The primary objective is to identify the validity level and feasibility of the model produced. Conducted as a research and development (R&D) study at SDN Kota Dumai, this project focuses on designing and refining a cooperative learning model grounded in moral principles to support curriculum implementation. Validation results show that the graphic design component obtained a score of 79.00, categorized as good; the linguistic aspect received a score of 78.00, also in the good category; and the content component earned a score of 83.00, likewise categorized as good. The implementation phase further demonstrated positive improvements. At SDN 002 Bagan Besar, the first trial resulted in a score of 78 (46.33%), which increased to 101 (59.83%) in the second trial and reached 134 (79.33%) in the third trial. Similarly, at SDN 004 Bagan, the first trial obtained a score of 61 (48.4%), rising to 80 (63.4%) in the second trial and increasing again to 91 (72%) in the third trial. These findings indicate that the moral-based cooperative learning model developed is both valid and reliable, and its use successfully enhances students’ interaction and learning outcomes.